Pengembangan Model Buku Ajar Fikih Moderat di Madrasah - Rozi, Syaikhu; Yaqin, Ainul; Saifuddin, Saifuddin; Rohmad, M. Ali; Syarif, M. (Proceedings of Annual Conference for Muslim Scholars, 2022)
The efforts of PAI teachers in realizing interesting, contextual and effective fiqh learning towards strengthening the character of moderate Muslims for madrasa students encountered obstacles, including the existence of textbooks that tended to be puritanical. In addition, most of the books used are only printed books with unattractive designs. For this reason, it is necessary to develop the process through development research (R&D) whose procedure uses the Plomp design (2010) with 5 stages, namely: 1) investigation, 2) design, 3) construction, 4) evaluation, 5) implementation. Meanwhile, so that the resulting textbooks can be more contextual and effective in strengthening the character of moderate Muslims for students, the textbooks are prepared by internalizing Indonesian Fiqh thinking with 2 choices of methods, namely: 1) the existing teaching materials are not changed, the content remains the same. with the discussion of classical Islamic books (books), but given additional contextualization explanations that are in accordance with Islamic moderation thinking, or b) teaching materials are changed in content according to the latest ijtihad of contemporary scholars and the creative traditions of Indonesian Muslim scholars who present law - Islamic law according to the situation and conditions of contemporary Muslim society.